2013
DOI: 10.3399/bjgp13x671579
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint of patient journeys through primary care: a mixed methods approach

Abstract: BackgroundThe NHS has a target of cutting its carbon dioxide (CO 2 ) emissions by 80% below 1990 levels by 2050. Travel comprises 17% of the NHS carbon footprint. This carbon footprint represents the total CO 2 emissions caused directly or indirectly by the NHS. Patient journeys have previously been planned largely without regard to the environmental impact. The potential contribution of 'avoidable' journeys in primary care is significant. AimTo investigate the carbon footprint of patients travelling to and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…The scope of other healthcare carbon footprinting studies has been an all‐encompassing audit of healthcare delivery that, again, assumes the environmental effect of individual clinical processes to be equivalent . This subset of research consistently finds the aggregate contribution of clinical processes to be one factor in assessments that also include non‐clinical processes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scope of other healthcare carbon footprinting studies has been an all‐encompassing audit of healthcare delivery that, again, assumes the environmental effect of individual clinical processes to be equivalent . This subset of research consistently finds the aggregate contribution of clinical processes to be one factor in assessments that also include non‐clinical processes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Every item in the operating room, including the surgeon, is transported there largely by fossil fuel‐consuming vehicles. The environmental effect of that transport and procurement has been thoroughly addressed in previous research . Our analysis also excludes the GHG emissions arising from the manufacture of capital goods used in the life cycle of the clinical process, as outlined in the BSI PAS 2050 guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The Estonian CRF06_cpx strain was likely originated in Africa (Zetterberg et al, 2004), and although it has been reported in other European countries, it is a minority variant in all studies performed outside Estonia. Conversely, subtype A dominates in Latvia and Lithuania, where the HIV-1 epidemic is otherwise very similar and driven by injecting drug use (Andrews et al, 2013;Popa et al, 2013). More recently CRF02_AG has been increasingly detected among PWID in Russia and is probably linked with the CRF02_AG epidemics in Central Asia (Bobkova, 2013).…”
Section: Eastern Europementioning
confidence: 95%
“…It was interesting to note that both authors of the article Initial management of dyspepsia in primary care were secondary care physicians. 1 In their otherwise practical approach to managing this common problem, no mention was made of upper gastrointestinal symptoms occasionally being the only early warning of possible ovarian malignancy. Many GPs would now consider arranging a CA125 blood test.…”
Section: Managing Dyspepsia In Primary Carementioning
confidence: 99%